2006
DOI: 10.1016/j.jcrs.2006.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Visual and refractive status at different focal distances after implantation of the ReSTOR multifocal intraocular lens

Abstract: Implantation of the ReSTOR IOL offered excellent visual acuity at distance and near distance and functional visual acuity in the intermediate range. For patients who need excellent vision at intermediate range, leaving 1 eye with distance myopia or hyperopia to compensate for intermediate vision may provide consistent good binocular vision over the full range in cases of bilateral implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 20 publications
8
91
1
4
Order By: Relevance
“…In our study, uncorrected intermediate visual acuity and best corrected far visual acuity among patients in the Restor™ group was in agreement with the results of Blaylock et al (25) , where mean visual acuity was 20/36 and 20/38 respectively. However, the same study found better intermediate visual acuity with monofocal SA60AT lenses compared to Restor™ lenses, which was not observed in our study for the assessed distances.…”
Section: Sn60at/sn60wf (N=32) Restor (N=16) Tecnis Mf (N=23) Independsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, uncorrected intermediate visual acuity and best corrected far visual acuity among patients in the Restor™ group was in agreement with the results of Blaylock et al (25) , where mean visual acuity was 20/36 and 20/38 respectively. However, the same study found better intermediate visual acuity with monofocal SA60AT lenses compared to Restor™ lenses, which was not observed in our study for the assessed distances.…”
Section: Sn60at/sn60wf (N=32) Restor (N=16) Tecnis Mf (N=23) Independsupporting
confidence: 93%
“…The good uncorrected near vision obtained in the Restor™ group can be explained by the fact that this lens has an addition power of +4.0 D in its diffractive structure (+3.5 diopters in the glasses plane). This may also explain the fact that corrected near vision was better in the Restor™ group, as the adding power in the monofocal group was limited to +3.0 D.In our study, uncorrected intermediate visual acuity and best corrected far visual acuity among patients in the Restor™ group was in agreement with the results of Blaylock et al (25) , where mean visual acuity was 20/36 and 20/38 respectively. However, the same study found better intermediate visual acuity with monofocal SA60AT lenses compared to Restor™ lenses, which was not observed in our study for the assessed distances.…”
supporting
confidence: 92%
“…In this study, the subjective near visual acuity of the ReSTOR group was better than that of the IQ group like in another study [1][2][3][4][5][6]. However, we could not prove this with objective tools such as OQAS.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies have evaluated the multifocal function of the ReSTOR by measuring the distance visual acuity and near visual acuity of patients who had cataract surgery with implantation of the lens. [1][2][3][4][5][6] However, they have a weakness in that they depend on the subjective visual acuity of the patients. Recently, Kim et al reported on the testing of the multifocal function of multifocal IOLs including ReSTOR using an optical bench system [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diffractive MF IOLs have concentric optical zones with different dioptric power, enabling patients to have good visual acuity at multiple focal points [3]. The drawbacks associated with this type of IOL design are loss of contrast sensitivity, increase in higher order aberrations, and night-time glare and halos [8,9]. Aychoua et al [10] recently reported a clinically relevant reduction of visual sensitivity as assessed with standard automated perimetry in patients with MF IOL.…”
Section: Discussionmentioning
confidence: 99%